Preparation technology of high-load fluorescent powder transparent film

Designing sandwich structures through rare earth ion doping preparation of upconversion sintered phosphor and organic polymers has been solved, and the dispersion and transparency of phosphor films are achieved, and transparent film preparation with high light transmittance and high brightness is achieved, suitable for LED luminescence conversion coating Application of layer materials.

CN119120023APending Publication Date: 2024-12-13UNIV OF JINAN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411256476.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the traditional transparent luminescent film preparation process, the uneven particle size and poor dispersion of the phosphor lead to uneven coating, making it difficult to achieve high light transmittance, and the high-powder-glue ratio film has problems such as high light scattering and low light transmission.

Method used

The upconverted sintered phosphor is prepared by rare earth ion doping, and the good dispersion in organic solvents is achieved by controlling the sintering conditions. The thin film structure of the sandwich structure is designed in combination with organic polymers to improve the dispersion and transparency of the phosphor and form a high load. .

Benefits of technology

It achieves a transparent film with high light transmittance (≥70%) and high fluorescence brightness, solving the light scattering problem of phosphor films. It has a simple process and high repeatability, and is suitable for large-scale mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119120023A_ABST
    Figure CN119120023A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation technology of a transparent film with high fluorescent powder loading capacity, and belongs to the technical field of functional film materials, fluorescent powder with excellent luminescence performance is obtained by combining solution method precursor synthesis with solid-phase sintering, and with 980nm up-conversion NaYF4: Yb: Er as an example, the size of luminescent particles ranges from hundreds of nanometers to several micrometers along with the rising of the sintering temperature. The increase of the particle size and the content of fluorescent powder in a colloidal solution seriously restricts the preparation of a transparent film. The invention aims to solve the problems of high light scattering and low light transmission of the film under the condition of large particle size. Dispersible up-conversion fluorescent powder is prepared through a solid-phase sintering method, and a high-transmittance and uniform-light-emitting transparent film is realized by designing a two-time or multi-time coating technology. The coating technology is wide in trial range, simple in operation process, high in repeatability and capable of achieving large-scale mass production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional film materials, and in particular relates to a transparent film preparation technology with high-loaded fluorescent powder. Background Art

[0002] Rare earth phosphor luminescent materials are a type of good light conversion materials. The main synthesis method is high-temperature solid-phase sintering, so as to obtain luminescent particles of different sizes and achieve good luminescent performance. Transparent luminescent materials mainly include inorganic materials such as oxides, fluorides, sulfides, and also organic polymers. Inorganic transparent luminescent materials generally have strict preparation conditions and require high-temperature sintering or hot pressing processes. Organic polymers can be used to prepare transparent luminescent materials by drop coating or spin coating under low temperature conditions, which is simpler to operate.

[0003] In recent years, transparent luminescent films have shown great development potential and application prospects in the fields of 3D display, LED luminescent conversion layer, and light absorption conversion protective layer in photovoltaic devices. The preparation of transparent films can be achieved by combining phosphors with polymers. The traditional preparation process of transparent films is to mix phosphors and epoxy resins evenly and then coat them. However, due to the uneven and large particle size of phosphor particles and their poor dispersibility in colloidal solutions, different degrees of precipitation will occur in the colloid, resulting in uneven phosphor coating and difficulty in achieving high light transmittance of the film. The brightness of the fluorescent film is positively correlated with the loading amount, but due to the problem of powder scattering, the development of fluorescent transparent films with high powder-to-gel ratios is still challenging. Summary of the invention

[0004] The present invention aims at the key problem of preparing highly transparent films by solid-phase sintering phosphors, and proposes and prepares a preparation technology of dispersible solid-phase phosphors and high-load transparent films, wherein the main component of the phosphor is fluoride, and up-conversion or down-transfer photoluminescence can be obtained by rare earth ion doping. The prepared phosphor achieves bright light emission under 980nm or ultraviolet excitation light irradiation, and achieves good dispersibility in organic solvents by controlling the sintering conditions, and can form a uniform transparent solution. Through refractive index engineering design and combining the thin film structure with organic polymer design, a high transmittance (80%) of a high-load phosphor film (25wt%) is achieved.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides an upconversion sintered phosphor, wherein the upconversion sintered phosphor is prepared by the following method:

[0007] (1) reacting a mixed rare earth metal oxide with concentrated nitric acid, adding a 0.04 g / ml NaF solution dropwise to obtain a precipitate, drying the precipitate, mixing it with NH4F and NaHCO3 in a mass ratio of 100:19:43, and grinding it to obtain a powder;

[0008] (2) The powder obtained in step (1) is sintered at 400-600° C. in a nitrogen atmosphere, washed with hydrochloric acid, deionized water, and ethanol in sequence, and dried at 60° C. for 3-6 hours to obtain an upconversion sintered phosphor.

[0009] The mixed rare earth metal oxide is a mixture of Y2O3, Yb2O3 and Er2O3 in a mass ratio of (2.98-3.0): (0.59-0.6): (0.12-0.15).

[0010] The second aspect of the present invention provides the use of the above-mentioned up-conversion sintered phosphor in the preparation of a transparent phosphor film.

[0011] According to a third aspect of the present invention, a fluorescent powder transparent film is provided, wherein the fluorescent powder transparent film is a sandwich structure.

[0012] In a fourth aspect, the present invention provides a method for preparing the above-mentioned fluorescent transparent film, comprising the following steps:

[0013] (1) dissolving the above-obtained upconversion sintered phosphor in a high polarity solution to obtain a phosphor dispersion, dissolving a polymer in the high polarity solution to obtain a polymer colloid solution, and mixing the phosphor dispersion with the polymer colloid solution to obtain a phosphor colloid solution;

[0014] (2) coating a layer of polymer colloid solution on a glass substrate, forming a polymer colloid layer after vacuum drying, coating a layer of phosphor colloid solution on the polymer colloid layer, forming a light conversion functional layer after vacuum drying, coating a layer of polymer colloid solution on the light conversion functional layer, and obtaining a fluorescent transparent film with a sandwich structure after vacuum drying.

[0015] The highly polar solution in step (1) is DMSO, DMF or acetonitrile.

[0016] The polymer in step (1) is one or a mixture of PMMA, PDMS, PU, ​​PVA, PS.

[0017] The powder-to-colloid ratio in the fluorescent powder colloidal solution of step (1) is ≥ 1:1.

[0018] The vacuum drying temperature in step (2) is 60-100° C., and the drying time is 6-12 hours.

[0019] The thickness of the fluorescent powder transparent film is less than 0.3 mm, and the transmittance of the fluorescent powder transparent film with a high powder-to-glue ratio is ≥70% in the entire visible light region.

[0020] In a fifth aspect, the present invention provides the use of the above fluorescent transparent film in the preparation of LED luminescence conversion coating materials.

[0021] Beneficial effects of the present invention:

[0022] The present invention provides a transparent film preparation technology with high phosphor load, which solves the problems of high light scattering and low light transmittance of phosphor films with large particle size, prepares dispersible up-conversion phosphors, and improves coating technology to prepare phosphor transparent films with high powder-to-glue ratio, and the film has excellent light transmittance effect. The preparation process of the phosphor transparent film provided by the present invention is simple, repeatable, wide in trial use, and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a technical flow chart of the preparation of the transparent fluorescent film.

[0024] Figure 2 This is the SEM image of the up-conversion sintered phosphor prepared in the present invention.

[0025] Figure 3 This is the XRD diagram of the up-conversion sintered phosphor prepared in the present invention.

[0026] Figure 4 It is a transmittance curve diagram of phosphor dispersions with different concentrations in the present invention.

[0027] Figure 5 It is a fluorescent powder transparent film prepared by the present invention; wherein the single-layer film is the fluorescent powder transparent film prepared in Example 2, the double-layer film is the fluorescent powder transparent film prepared in Example 3, and the triple-layer film is the fluorescent powder transparent film prepared in Example 5.

[0028] Figure 6 The spectrum diagram and fluorescence luminescence photograph of the transparent film of phosphor prepared in Example 6. DETAILED DESCRIPTION

[0029] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0030] As mentioned above, transparent luminescent films have good optical properties and thermal stability, and have broad application prospects in various fields, and are gradually gaining attention from researchers. In the prior art, in order to ensure the fluorescent brightness of transparent luminescent films, it is necessary to increase the content of phosphor in the film or increase the thickness of the film, but this process will greatly reduce the transmittance of the film, and due to the poor dispersibility of solid-phase sintered phosphors in different solutions, it will cause different degrees of precipitation in the colloid, resulting in uneven phosphor coating, making it difficult to achieve high transmittance of the film, thus seriously affecting the development of transparent luminescent films.

[0031] Based on this, the present invention provides a preparation technology for a transparent film with a high loading of phosphor, including two parts: solid-phase sintering phosphor preparation and transparent luminescent film preparation technology. The phosphors involved in the high loading transparent phosphor film prepared by the present invention are independently synthesized in the laboratory, including up-conversion sintering phosphors and down-conversion sintering phosphors. The up-conversion sintering phosphor prepared by the present invention has excellent dispersibility when dissolved in a high polarity solution at different concentrations, and the obtained phosphor dispersion has good transparency. Compared with the prior art, the phosphor colloid solution obtained by mixing the phosphor dispersion with the polymer colloid solution greatly improves the powder-to-gel ratio in the phosphor colloid solution, and further improves the fluorescent brightness of the prepared transparent luminescent film.

[0032] The present invention designs the structure of the film by manipulating the coating technology, and prepares a fluorescent powder transparent film with high transmittance and uniform luminescence. The transparent film structure designed by the present invention includes single-layer, double-layer and triple-layer structures, wherein the single-layer structure is to coat only the fluorescent powder colloidal solution on the glass substrate, and after vacuum drying, a single-layer fluorescent powder transparent film containing only the fluorescent powder colloidal layer is formed; the double-layer structure is to coat a layer of fluorescent powder colloidal solution with a high powder-to-colloid ratio on the glass substrate, and after vacuum drying, a light conversion functional layer is formed, and at this time, the film is not transparent, and then a layer of polymer colloidal solution is coated on the light conversion functional layer, and after vacuum drying, a double-layer fluorescent powder transparent film is formed; the triple-layer structure is to coat a layer of polymer colloidal solution on the glass substrate, and after vacuum drying, a polymer colloidal layer is formed, and a layer of fluorescent powder colloidal solution is coated on the polymer colloidal layer, and after vacuum drying, a light conversion functional layer is formed, and a layer of polymer colloidal solution is coated on the light conversion functional layer, and after vacuum drying, a triple-layer fluorescent powder transparent film with excellent light transmission performance is obtained.

[0033] The present invention improves the preparation process of fluorescent powder transparent film, and provides up-conversion sintered fluorescent powder and down-conversion sintered fluorescent powder, which can be used to prepare transparent film with high transmittance. During preparation, the fluorescent powder is first dissolved in a high polarity solution to obtain a transparent and uniform fluorescent powder dispersion, which avoids the precipitation problem caused by the large fluorescent powder particle size being directly dissolved in the colloidal solution, and makes the fluorescent powder coating and the light conversion functional layer uniform to a certain extent. Due to the presence of the fluorescent powder, the light conversion functional layer cannot be completely smooth, so the single-layer transparent film prepared by simply coating a layer of fluorescent powder colloidal solution with a high powder-to-colloid ratio has the problems of high light scattering and low light transmittance. Based on this, the coating process is further improved, and the prepared two-layer transparent film and three-layer transparent film have better surface flatness due to the coating of polymer colloidal solution on the upper or / and lower surface of the light conversion functional layer to form a polymer colloidal layer, which reduces the light scattering on the surface of the transparent film, and can realize the effective conduction of light beams between films, thereby achieving high transmittance of the film.

[0034] The transparent film provided by the present invention still has good light transmittance when the phosphor content and the film thickness are increased, and ensures the high transmittance of the film while ensuring the fluorescent brightness of the film, and provides a feasible preparation method for developing a phosphor transparent film with a high powder-to-glue ratio.

[0035] The following detailed description is for illustrative purposes only and is intended to provide further explanation of the present application, rather than to limit the scope of the present invention.

[0036] In the embodiment of the present invention, the transparent properties of the transparent film are characterized by placing the prepared film on a substrate with a background pattern, observing the information of the substrate, and recording it with a camera. The transmittance of the transparent film in the embodiment is obtained by attaching the prepared film to the test platform of the spectrometer for detection, wherein the transmittance calculation formula is: T(%) = I / I0, I is the transmitted light intensity, and I0 is the incident light intensity. The transmittance of the phosphor dispersion in the embodiment is measured on the test platform of the spectrometer with DMSO as the baseline, and on this basis, the polar transmittance of the phosphor dispersion containing different masses is measured.

[0037] Example 1: Preparation of sintered phosphor

[0038] (1) Preparation of upconversion sintered phosphors

[0039] Weigh 2.98g Y2O3, 0.59g Yb2O3 and 0.12g Er2O3, mix evenly, add 9ml concentrated nitric acid solution, then add 6ml deionized water, put into a hydrothermal kettle and heat at 160℃ for 4h, then cool naturally to obtain a colorless nitrate solution, add 0.04g / ml NaF solution dropwise to the nitrate solution, react to obtain a precipitate, centrifuge, wash and dry the precipitate.

[0040] The dried precipitate was mixed with NH4F and NaHCO3 in a mass ratio of 100:19:43 and ground to obtain a white powder. The obtained white powder was sintered at 400°C for 1 hour in a nitrogen atmosphere, washed with 1 mol / L hydrochloric acid, deionized water, and ethanol solution at 8000 rpm for 5 minutes, and dried at 60°C for 3 hours to obtain an up-conversion sintered phosphor with a particle size of 0.5um to 10um. The SEM image is shown in FIG. Figure 2 As shown in Figure 2, after sintering at 500℃, a regular rod-shaped upconversion luminescent body is formed. The corresponding XRD pattern is shown in Figure 2. Figure 3 As shown, it exhibits a good hexagonal crystal structure, where the 2θ angles of 17.204, 30.063, 30.785, 34.826, 39.672, 43.494, 46.610, 52.036, 53.277, 53.750, 55.186, 61.119, 62.351, and 63.734 correspond to (1 0 0), (1 1 0), (1 0 1), (2 0 0), (1 1 1), (2 0 1), (2 1 0), (0 0 2), (3 0 0), (2 1 1), (1 0 2), (1 1 2), (2 2 0), and (2 0 2) crystal planes, respectively.

[0041] 50 mg, 100 mg, and 200 mg of upconversion sintered phosphors were weighed, respectively, and dissolved in 1 mL of DMSO solution and ultrasonically stirred to obtain phosphor dispersions of different concentrations. The transmittance of the three concentrations of phosphor dispersions was tested. The test results showed that the phosphor prepared by the present invention had good dispersibility in polar solutions, and the phosphor dispersion had good transparency and excellent light transmission performance ( Figure 4 ).

[0042] (2) Preparation of Downward Transfer Sintering Phosphor

[0043] Weigh 3.06g Y(NO3)3·6H2O, 0.45g Tb(NO3)3·6H2O, and 0.45g Gd(NO3)3·6H2O, add appropriate amount of deionized water to dissolve, and add 0.04g / ml NaF solution dropwise. The reaction obtains a precipitate, which is centrifuged, washed, and dried. The subsequent preparation process of the down-conversion sintered phosphor is the same as that of the up-conversion phosphor, as follows:

[0044] The dried precipitate was mixed with NH4F and NaHCO3 in a mass ratio of 100:19:43 and ground to obtain a white powder. The white powder was sintered at 400°C for 1 h in a nitrogen atmosphere, washed with 1 mol / L hydrochloric acid, deionized water, and ethanol solution, centrifuged at 8000 rpm for 5 min, and dried at 60°C for 3 h to obtain a downward transfer sintered phosphor.

[0045] Example 2: Preparation of a single-layer transparent film

[0046] (1) Weigh 50 mg of the up-conversion sintered phosphor prepared in Example 1, dissolve it in 1 mL of DMSO solution, stir and ultrasonicate to obtain a phosphor dispersion.

[0047] (2) Take 2.5 g of PMMA and dissolve it in 15 ml of DMSO solution to obtain a polymer colloid solution with a concentration of 15 wt%.

[0048] (3) 333 mg of the polymer colloid solution obtained in step (2) was mixed with the fluorescent dispersion obtained in step (1) to prepare a fluorescent powder colloid solution with a powder-to-gel ratio of 1:1.

[0049] (3) The entire phosphor colloidal solution was coated on a 40×40 mm glass substrate and vacuum dried at 80° C. and −0.08 MPa for 3 h to obtain a single-layer phosphor transparent film. The film in this embodiment was tested for transmittance in the visible light region of 300 nm to 800 nm, and the visible light transmittance was 58% to 61%.

[0050] Example 3: Preparation of a double-layer transparent film

[0051] (1) Weigh 50 mg of the up-conversion sintered phosphor prepared in Example 1, dissolve it in 1 mL of DMSO solution and stir it ultrasonically to obtain a phosphor dispersion.

[0052] (2) Take 2.5 g of PMMA and dissolve it in 15 ml of DMSO solution to obtain a polymer colloid solution with a concentration of 15 wt%.

[0053] (3) 333 mg of the polymer colloid solution obtained in step (2) was mixed with the fluorescent dispersion obtained in step (1) to prepare a fluorescent powder colloid solution with a powder-to-gel ratio of 1:1.

[0054] (4) A layer of phosphor colloidal solution was first coated on a 40×40 mm glass substrate. The coating amount was the entire mixed solution in (3), and vacuum dried at 80° C. and −0.08 MPa for 3 h to obtain a phosphor colloidal layer.

[0055] (5) A layer of polymer colloid solution is coated on the phosphor colloid layer obtained in step (4) in an amount of 120 mg. The film is dried in a vacuum oven at 80°C and -0.08 MPa for 3 h to obtain a double-layer transparent film. The film in this embodiment is tested for transmittance in the visible light region of 300nm-800nm, and the visible light transmittance is 80%-83%.

[0056] Example 4: Preparation of a double-layer transparent film

[0057] (1) Weigh 100 mg of the up-conversion sintered phosphor prepared in Example 1, dissolve it in 1 mL of DMSO solution and stir it ultrasonically to obtain a phosphor dispersion.

[0058] (2) Take 2.5 g of PMMA and dissolve it in 15 ml of DMSO solution to obtain a polymer colloid solution with a concentration of 15 wt%.

[0059] (3) 167 mg of the polymer colloid solution obtained in step (2) was mixed with the phosphor dispersion obtained in step (1) to prepare a phosphor colloid solution with a powder-to-gel ratio of 4:1.

[0060] (4) A layer of phosphor colloidal solution was first coated on a 40×40 mm glass substrate, the coating amount of which was the entire mixed dispersion in (3), and vacuum dried at 80° C. and −0.08 MPa for 3 h to obtain a phosphor colloidal layer.

[0061] (5) A layer of polymer colloid solution is coated on the phosphor colloid layer obtained in step (4) with a coating amount of 120 mg, and vacuum dried at 80° C. and −0.08 MPa for 3 h to obtain a double-layer transparent film.

[0062] The film described in this embodiment was tested for transmittance in the visible light region. In the visible light region of 300nm-800nm, the visible light transmittance was 55%-60%.

[0063] Example 5: Preparation of three-layer transparent film

[0064] (1) Weigh 50 mg of the up-conversion sintered phosphor prepared in Example 1, dissolve it in 1 mL of DMSO solution and stir it ultrasonically to obtain a phosphor dispersion.

[0065] (2) Take 2.5 g of PMMA and dissolve it in 15 ml of DMSO solution to obtain a polymer colloid solution with a concentration of 15 wt%.

[0066] (3) 333 mg of the polymer colloid solution obtained in step (2) was mixed with the fluorescent dispersion obtained in step (1) to prepare a fluorescent powder colloid solution with a powder-to-gel ratio of 1:1.

[0067] (4) A layer of polymer colloid solution is first coated on a 40×40 mm glass substrate, the coating amount is 120 mg, and vacuum drying is performed at 80°C and -0.08 MPa for 3 h to obtain a polymer colloid layer. A layer of phosphor colloid solution is coated on the polymer colloid layer, the coating amount is the entire mixed dispersion in step (3), and vacuum drying is performed at 80°C and -0.08 MPa for 3 h to obtain a light conversion functional layer. A layer of polymer colloid solution is coated on the light conversion functional layer, the coating amount is 120 mg, and vacuum drying is performed at 80°C and -0.08 MPa for 3 h to obtain a three-layer phosphor transparent film with a sandwich structure. The film in this embodiment is tested for transmittance in the visible light region of 300nm-800nm, and its visible light transmittance is 89%-92%.

[0068] Example 6: Preparation of three-layer transparent film

[0069] (1) Weigh 100 mg of the up-conversion sintered phosphor prepared in Example 1, dissolve it in 1 mL of DMSO solution and stir it ultrasonically to obtain a phosphor dispersion.

[0070] (2) Take 2.5 g of PMMA and dissolve it in 15 ml of DMSO solution to obtain a polymer colloid solution with a concentration of 15 wt%.

[0071] (3) 167 mg of the polymer colloid solution obtained in step (2) was mixed with the fluorescent dispersion obtained in step (1) to prepare a fluorescent powder colloid solution with a powder-to-gel ratio of 4:1.

[0072] (4) A layer of polymer colloid solution was first coated on a 40×40 mm glass substrate, the coating amount was 120 mg, and vacuum dried at 80°C and -0.08 MPa for 3 h to obtain a polymer colloid layer. A layer of phosphor colloid solution was coated on the polymer colloid layer, the coating amount was the entire mixed dispersion in (3), and vacuum dried at 80°C and -0.08 MPa for 3 h to obtain a light conversion functional layer. A layer of polymer colloid solution was coated on the light conversion functional layer, the coating amount was 120 mg, and vacuum dried at 80°C and -0.08 MPa for 3 h to obtain a three-layer transparent phosphor film with a sandwich structure, and the transmittance test result in the visible light region of 300nm-800nm ​​was 75%-78%.

[0073] The light transmittance of the fluorescent powder transparent film with a high powder-to-glue ratio prepared by the present invention in the visible light region is compared with that of the fluorescent powder transparent film with a powder-to-glue ratio of 1:1 prepared in Example 5, although the light transmittance is reduced to a certain extent, it still reaches more than 70%, and has good application prospects. The fluorescent powder transparent film with a powder-to-glue ratio of 4:1 prepared by the present invention has excellent luminous properties and good light transmittance, and provides a feasible preparation method for the development of fluorescent powder transparent films with a high powder-to-glue ratio.

[0074] Example 7: Preparation of three-layer transparent film of downward transfer sintered phosphor

[0075] (1) Weigh 50 mg of the downward transfer sintered phosphor prepared in Example 1, dissolve it in 1 mL of DMSO solution and stir it ultrasonically to obtain a downward transfer phosphor dispersion.

[0076] (2) Take 2.5 g of PMMA and dissolve it in 15 ml of DMSO solution to obtain a polymer colloid solution with a concentration of 15 wt%.

[0077] (3) 333 mg of the polymer colloid solution obtained in step (2) was mixed with the downward-transferred fluorescent dispersion obtained in step (1) to prepare a downward-transferred fluorescent powder colloid solution with a powder-to-gel ratio of 1:1.

[0078] (4) A layer of polymer colloid solution was first coated on a 25×25 mm glass substrate, the coating amount was 100 mg, and vacuum dried at 80°C and -0.08 MPa for 3 h to obtain a polymer colloid layer. A layer of down-transfer phosphor colloid solution was coated on the polymer colloid layer, the coating amount was the entire mixed dispersion in (3), and vacuum dried at 80°C and -0.08 MPa for 3 h to obtain a light conversion functional layer. A layer of polymer colloid solution was coated on the light conversion functional layer, the coating amount was 100 mg, and vacuum dried at 80°C and -0.08 MPa for 3 h to obtain a sandwich structure down-transfer phosphor film. The transmittance of the down-transfer phosphor film in this embodiment was tested in the visible light region of 300nm-800nm, and its visible light transmittance was 65%-75%.

[0079] Therefore, the down-transfer phosphor provided by the present invention can also realize the preparation of transparent films, and the transmittance of the down-transfer phosphor film prepared using the down-transfer phosphor can reach more than 70% in part of the visible light region, still showing good light transmission performance.

[0080] Comparative Example 1: Preparation of three-layer transparent film

[0081] (1) Weigh 200 mg of the up-conversion sintered phosphor prepared in Example 1, dissolve it in 2 mL of DMSO solution and stir it ultrasonically to obtain a phosphor dispersion.

[0082] (2) Take 2.5 g of PMMA and dissolve it in 15 ml of DMSO solution to obtain a polymer colloid solution with a concentration of 15 wt%.

[0083] (3) A layer of polymer colloid solution was first coated on a 40×40 mm glass substrate, the coating amount was 120 mg, and vacuum dried at 80°C and -0.08 MPa for 3 h to obtain a polymer colloid layer. A layer of phosphor dispersion was coated on the polymer colloid layer, the coating amount was 267 mg, and vacuum dried at 80°C and -0.08 MPa for 3 h to obtain a phosphor layer. A layer of polymer colloid solution was coated on the phosphor layer, the coating amount was 120 mg, and vacuum dried at 80°C and -0.08 MPa for 3 h to obtain a three-layer transparent phosphor film. The transmittance of the phosphor transparent film in Comparative Example 1 was tested in the visible light region of 300nm-800nm, and its visible light transmittance was 45%-50%.

[0084] The light transmittance of the three-layer transparent phosphor film of Comparative Example 1 is reduced to a certain extent compared with the light transmittance of the transparent film prepared in Example 6. The test results show that by optimizing the preparation method of the phosphor transparent film and mixing the prepared phosphor dispersion with the colloidal solution, the coating can be made uniform to a certain extent, the light scattering on the surface of a part of the transparent film can be reduced, the conduction of the light beam between the films can be improved, and the transmittance of the phosphor transparent film can be further improved.

[0085] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. An up-conversion sintered phosphor, characterized in that: The up-conversion sintered phosphor is prepared by the following method: (1) reacting a mixed rare earth metal oxide with concentrated nitric acid, adding a 0.04 g / ml NaF solution dropwise to obtain a precipitate, drying the precipitate, mixing it with NH4F and NaHCO3 in a mass ratio of 100:19:43, and grinding it to obtain a powder; (2) The powder obtained in step (1) is sintered at 400-600° C. in a nitrogen atmosphere, washed with hydrochloric acid, deionized water, and ethanol in sequence, and dried at 60° C. for 3-6 hours to obtain an upconversion sintered phosphor.

2. The up-conversion sintered phosphor according to claim 1, characterized in that: The mixed rare earth metal oxide is a mixture of Y2O3, Yb2O3 and Er2O3 in a mass ratio of (2.98-3.0): (0.59-0.6): (0.12-0.15).

3. Use of the up-conversion sintered phosphor according to claim 1 in preparing a phosphor transparent film.

4. A fluorescent powder transparent film, characterized in that: The fluorescent powder transparent film is a sandwich structure.

5. The method for preparing the fluorescent powder transparent film according to claim 4, characterized in that: The steps include: (1) dissolving the up-conversion sintered phosphor obtained in claim 1 in a high polarity solution to obtain a phosphor dispersion, dissolving a polymer in the high polarity solution to obtain a polymer colloid solution, and mixing the phosphor dispersion with the polymer colloid solution to obtain a phosphor colloid solution; (2) coating a layer of polymer colloid solution on a glass substrate, forming a polymer colloid layer after vacuum drying, coating a layer of phosphor colloid solution on the polymer colloid layer, forming a light conversion functional layer after vacuum drying, coating a layer of polymer colloid solution on the light conversion functional layer, and obtaining a fluorescent transparent film with a sandwich structure after vacuum drying.

6. The method for preparing a fluorescent powder transparent film according to claim 5, characterized in that: The highly polar solution in step (1) is DMSO, DMF or acetonitrile.

7. The method for preparing a fluorescent transparent film according to claim 5, characterized in that: The polymer in step (1) is one or a mixture of PMMA, PDMS, PU, ​​PVA, PS.

8. The method for preparing a fluorescent transparent film according to claim 5, characterized in that: The powder-to-colloid ratio in the fluorescent powder colloidal solution of step (1) is ≥ 1:

1.

9. The method for preparing a fluorescent powder transparent film according to claim 5, characterized in that: The vacuum drying temperature in step (2) is 60-100° C., and the drying time is 6-12 hours.

10. Use of the fluorescent powder transparent film according to claim 4 in preparing LED luminescence conversion coating materials.